2013
DOI: 10.1007/s00264-013-2096-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance mapping of the rim of articular cartilage defects of the patella

Abstract: Purpose Elevated T2-values of articular cartilage are associated with an increase in cartilage water that results from a damaged collagen matrix, and provide a marker for cartilage damage. We used T2 mapping to analyse the rim of cartilage defects that appeared to be intact on the morphological sequences, to determine whether there are early biochemical changes already present. Method We calculated T2 values for the rim of cartilage defects in 25 patients and compared these values to another area of control ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Koller [23] showed T2 mapping is an appropriate tool for the accurate staging of cartilage. While morphological imaging, even when performed with a high-resolution protocol, can show intact cartilage adjacent to a cartilage defect, T2 mapping can show signs of cartilage degeneration in the deep zone.…”
Section: Discussionmentioning
confidence: 99%
“…Koller [23] showed T2 mapping is an appropriate tool for the accurate staging of cartilage. While morphological imaging, even when performed with a high-resolution protocol, can show intact cartilage adjacent to a cartilage defect, T2 mapping can show signs of cartilage degeneration in the deep zone.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such methodological tools include nuclear magnetic resonance imaging (Koller et al, 2014), polarization light microscopy (Panula et al, 1998), laser-scanning microscopy and autoradiography (Buschmann et al, 1996;Kawaguchi et al, 2012). The value of the data gleaned using these approaches is compromised by the limited resolution of the images, which lies within the light-microscopic range.…”
Section: Special Proceduresmentioning
confidence: 98%
“…The anisotropic organization of the coarser collagenous fibrils can be revealed also by implementing specific stains, such as Sirius Red (Junqueira et al, 1980), as well as by polarized light microscopy (Mittelstaedt et al, 2011) and by magnetic resonance imaging (Momot et al, 2010;Koller et al, 2014), or by an analysis of birefringence (Panula et al, 1998). Scanning electron microscopy is the least useful methodology.…”
Section: The Network Of Fibrillar Collagensmentioning
confidence: 99%
“…The quantitative T2 mapping technique [23] represents a sensitive MR technique that provides information on the interaction between the extracellular matrix and water molecules of the cartilage. Healthy cartilage shows increasing T2 values from the deep to the superficial zone of the cartilage [24][25][26][27][28][29]. It has been shown that increased T2 values indicate damage in the collagen construct, reflecting the increased water mobility [25,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy cartilage shows increasing T2 values from the deep to the superficial zone of the cartilage [24][25][26][27][28][29]. It has been shown that increased T2 values indicate damage in the collagen construct, reflecting the increased water mobility [25,[30][31][32]. T2 mapping is, therefore, an ideal marker to detect and monitor progression of osteoarthritis [33].…”
Section: Introductionmentioning
confidence: 99%